2006
DOI: 10.1353/mcb.2006.0087
|View full text |Cite
|
Sign up to set email alerts
|

Money and Risk Sharing

Abstract: We study the use of money for sharing consumption risk. In our model, agents randomly receive endowments at some points in time and produce at other points. Due to information frictions, agents cannot use intertemporal contracts to share risk. The use of money allows agents to overcome these information frictions. The Friedman rule is shown to generate efficient risk sharing. Furthermore, we quantify the welfare costs of incomplete risk sharing and find that with 10% inflation, the welfare cost of inefficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
18
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…Although different in its objectives, their analysis also relies on the lack of consumption insurance. Our work is also related to a large number of papers that have explored the implications of different monetary regimes for risk sharing in environments with idiosyncratic risk (e.g., Aiyagari and Williamson (2000), Reed and Waller (2006)), and is related to Rocheteau and Wright (2005) for the use of competitive pricing à la Lucas and Prescott (1974) in a money search model.…”
mentioning
confidence: 99%
“…Although different in its objectives, their analysis also relies on the lack of consumption insurance. Our work is also related to a large number of papers that have explored the implications of different monetary regimes for risk sharing in environments with idiosyncratic risk (e.g., Aiyagari and Williamson (2000), Reed and Waller (2006)), and is related to Rocheteau and Wright (2005) for the use of competitive pricing à la Lucas and Prescott (1974) in a money search model.…”
mentioning
confidence: 99%
“…The paper is related to the long literature on the role of money in incomplete insurance markets from the seminal work of Bewley (1980) to recent and important contributions by Aiyagari and Williamson (2000), Faig (2000), Akyol (2004) and Reed and Waller (2006) amongst others. In these models, agents hold fiat money to smoothen consumption over time and state in the face of idiosyncratic risks.…”
Section: Introductionmentioning
confidence: 99%
“…This paper investigates the dual role of money as a self‐insurance device (store of value) and a means of payment when institutional arrangements do not allow for perfect risk sharing because the set of securities is incomplete and the implementation of risk sharing contracts is limited by a lack of commitment. A number of studies, like Scheinkman and Weiss (1986) and Reed and Waller (2006), have suggested that when it is costless to hold money it is possible to obtain perfect risk sharing. These studies, however, have in common two related features.…”
mentioning
confidence: 99%
“…There are three papers that are especially related to ours. Reed and Waller (2006) also consider a variant of the LW framework where agents face uninsurable risks. In their paper, the risk that agents face is a consumption risk due to shocks to their endowments, and they ask whether money can play the role of insuring against consumption risk.…”
mentioning
confidence: 99%
See 1 more Smart Citation